Plotino y el problema del yo: una aproximación a su antropología filosófica a través del estudio del mal - Román Molero, Massiel (2019)
The purpose of this paper is to present an approach to Plotinus’ anthropology by addressing the levels (or layers) of the self from a problematization of the conception of evil –metaphysical and ethical– expressed mainly in the Enneads V 1, 1, 1-15 and I 8, 3, 35-40. For this, in the first section the role of matter in the procession will be briefly reviewed. In the second section, I will focus on the study of the problem between the metaphysical and ethical conceptions of evil, and its relation to the levels of the self. In the last section, I will address the question regarding the epistemic value of the existence of evil for the philosopher in the dialectical distinction of the true self of the human being.